The relationship between overweight/obesity and dental erosion among a group of Saudi children and adolescents - Nahla Jastaniyah; Ibrahim Al-Majed; Aayed Alqahtani (Indian Journal of Dental Research, 2019)
Background: As childhood obesity is emerging in Saudi children and adolescents with high prevalence, it is considered as one of the major public health concerns. Therefore, it has been studied in relation to other diseases as a cause factor. Aim: The aim of this study is to investigate whether childhood obesity is a risk indicator for dental erosion and to obtain information on dietary habits that are related to dental erosion in overweight/obesity in a group of Saudi children and adolescents. Study Design: The study involved 370 children of both genders aged 4-18 years. The convenient sample included 190 overweight/obese children attending obesity clinic and 180 controls. Materials and Methods: Body mass index (BMI) (kg/m2) was calculated and BMI percentile obtained based on the age- and sex-specific according to the Centers for Disease Control chart (normal 5th to <85th percentile, overweight 85th to <95th percentile, and obese ≥95th percentile). Dental examination and questionnaire were carried out by one calibrated and trained examiner on these children using the UK Children's Dental Health Survey Classification for dental erosion. Results: The prevalence of dental erosion was more significant in the study group (8.42%) than the normal group (2.78%). Its severity was higher in the form of loss of enamel surface characterization in the study group (86.36%) compared to controls (13.64%). Carbonated drinks that were taken at night and drinks that were taken at night and drunk without a straw showed higher prevalence of dental erosion (33.3% and 10.3%) in overweight/obese participants. Conclusions: Dental erosion can be regarded as a risk indicator of childhood obesity in the form of loss of enamel surface characterization. Efforts should be taken to reduce carbonated drinks intake and to change the method of drinking erosive potential drinks among overweight/obese children.